Genome sequencing with comprehensive variant calling identifies structural variants and repeat expansions in a large fraction of individuals with ataxia and/or neuromuscular disorders - Ek, Marlene; Nilsson, Daniel; Engvall, Martin; Malmgren, Helena; Thonberg, Håkan; Pettersson, Maria; Anderlid, Britt-Marie; Hammarsjö, Anna; Helgadottir, Hafdis T.; Arnardottir, Snjolaug; Naess, Karin; Nennesmo, Inger; et al. (Frontiers in Neurology, 2023)
Introduction: Neuromuscular disorders (NMDs) have a heterogeneous etiology. A genetic diagnosis is key to personalized healthcare and access to targeted treatment for the affected individuals. Methods: In this study, 861 patients with NMDs were analyzed with genome sequencing and comprehensive variant calling including single nucleotide variants, small insertions/deletions (SNVs/INDELs) and structural variants (SVs) in a panel of 895 NMD genes, as well as short tandem repeat expansions (STRs) at 28 loci. In addition, for unsolved cases with an unspecific clinical presentation, analysis of a panel with OMIM disease genes was added. Results: In the cohort, 27% (232/861) of the patients harbored pathogenic variants, of which STRs and SVs accounted for one third (71/232. The variants were found in 107 different NMD genes. Furthermore, 18 pediatric patients harbored pathogenic variants in non-NMD genes. Discussion: Our results highlight that for children with unspecific hypotonia, a genome wide analysis rather than a disease-based gene panel, should be considered as a diagnostic approach. More importantly, our results clearly show that it is crucial to include STR- and SV-analyses in the diagnostics of patients with neuromuscular disorders.